ESTIMATION OF THE PRODUCTION COSTS OF 67Ga, 201Tl, 123I AND 111In MEDICALLY IMPORTANT RADIOISOTOPES BY A CYCLOTRON FACILITY TO BE INSTALLED AT ANKARA NUCLEAR RESEARCH AND TRAINING CENTRE IN TURKEY - Turhan, Şeref (Ankara Nuclear Research and Training Centre (ANRTC)06100 Besevler Ankara, 2000)
A cyclotron with the proton beam current of 100 µA and a variable proton energy range of 15 30 MeV is planned to install at ANRTC to produce the medically important radioisotopes 67Ga, 201Tl, 123I and 111In, imported for the need of Turkey. In this work, the annually production rates 170 Ci for 67Ga, 303 Ci for 201Tl, 283 Ci for 123I and 325 Ci for 111In have been calculated theoretically. Also the production costs have been estimated to be 2.7 $/mCi for 67Ga, 2.9 $/mCi for 201Tl, 3.3 $/mCi for 123I and 0.6 $/mCi for 111In levelized ten years facility amortization. It has been seen that the calculated production costs for these radioisotopes will be less than their import prices.
Keywords: Estimation, Medically important, Nuclear research